SOCIALIZATION OF BENEFITS OF ULTRASOUND, FE, AND HEALTHY FOOD FOR PREGNANT WOMEN AND ELEMENTARY SCHOOL CHILDREN - Nurhasanah; Eka Ratnasari; Fika Nurul Hidayah; Teguh Adiyas Putra; Sherly Marshelia; Rizky Putri Ramadhan; Arofah Firda Rahmah; Euis Nurkholifah Mahendra; Nesta (Ann Publisher, 2024)
The objectives of the KKN Stikes Muhammadiyah Cirebon activity are 1. To find out the knowledge of pregnant women about ultrasound examinations and compliance with the use of Fe 2 tablets. To increase the knowledge of pregnant women about the fetus about the importance of ultrasound examination and its consumption of Fe. The importance of a healthy and nutritious diet. The specific goals to be achieved include increasing public knowledge, understanding and awareness, especially pregnant women and children, about healthy diets. The results that Salam Village, Sarewu Village RW 03, Pancalang District, Kuningan Regency, especially pregnant women with ultrasound knowledge and agricultural counseling, were held on February 13 and 15, 2023 at the Sarewu Village Health Center and Sarewu Elementary School, targeting pregnant women and elementary school children. The enthusiasm of pregnant women and students is quite good, some pregnant women have had ultrasounds and take Fe tablets. Primary school students also responded quite positively, showing optimal cognitive development and most had a stable weight despite experiencing growth. Family participation plays a very important role in caring for and assisting pregnant women and children in meeting the nutritional needs and development of pregnancy.